Motivational engagement in first-time hearing aid users: a feasibility study - Ferguson, Melanie A.; Maidment, David; Russell, Naomi; Gregory, Melanie; Nicholson, Richard (Taylor & Francis, 2016)
Objective: To assess (1) the feasibility of incorporating the Ida Institute’s Motivation Tools into a UK audiology service, (2) the potential benefits of motivational engagement in first-time hearing aid users, and (3) predictors of hearing aid and general health outcome measures. Design: A feasibility study using a single-centre, prospective, quasi-randomized controlled design with two arms. The Ida Institute’s Motivation Tools formed the basis for motivational engagement. Study sample: First-time hearing aid users were recruited at the initial hearing assessment appointment. The intervention arm underwent motivational engagement (M+, n = 32), and a control arm (M-, n = 36) received standard care only. Results: The M+ group showed greater self-efficacy, reduced anxiety, and greater engagement with the audiologist at assessment and fitting appointments. However, there were no significant between-group differences 10-weeks post-fitting. Hearing-related communication scores predicted anxiety, and social isolation scores predicted depression for the M+ group. Readiness to address hearing difficulties predicted hearing aid outcomes for the M- group. Hearing sensitivity was not a predictor of outcomes. Conclusions: There were some positive results from motivational engagement early in the patient journey. Future research should consider using qualitative methods to explore whether there are longer-term benefits of motivational engagement in hearing aid users.